Regenerated hard alloy material for round rod and preparation method thereof
By reducing the amount of native tungsten carbide and adopting the mutual cooperation of regenerated tungsten carbide, zinc melt and cobalt powder with a specific ratio, the sintering process is formed, which solves the difficulty of existing tungsten carbide-based carbide-based carbide-based carbide-based carbide-based carbide-hard carbide at the same time and is difficult to achieve high hardness and high speed at the same time. The problem of bending strength has achieved economical and efficient preparation of cemented carbide.
Patent Information
- Application Number
- CN202411530188.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for existing tungsten carbide-based cemented carbide to achieve high hardness and high bending strength at the same time, and the production costs are high, which affects the sustainable development of the industry.
By reducing the amount of native tungsten carbide, the regenerated tungsten carbide, zinc melt and cobalt powder with specific mass and Fischer particle size are combined, and the regenerated tungsten carbide and zinc melt of different contents and particle sizes are combined, and the sintering process is used to form a denser , thereby improving the flexural strength of the alloy.
It realizes high hardness and high bending strength of cemented carbide, and effectively reduces production costs, is suitable for large-scale production, and makes full use of waste, reducing resource waste and environmental pollution.
Smart Images

Figure CN119392078A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of cemented carbide preparation, and specifically relates to a recycled cemented carbide material for round rods and a production method thereof. Background Art
[0002] Cemented carbide round rod is also called tungsten steel round rod, or simply tungsten steel round rod or cemented carbide round rod. Cemented carbide is a composite material composed of refractory metal compounds (hard phase) and bonding metals (bonding phase) produced by powder metallurgy. Cemented carbide rods are mainly used in the manufacture of metal cutting tools, wood, plastics and other industries that require hardness, wear resistance and corrosion resistance. The main features of cemented carbide rods are stable mechanical properties, easy welding, high wear resistance and high impact resistance. Among them, tungsten carbide is the main raw material for tungsten-based cemented carbide rods, and tungsten resources are strategic metal resources with high value. As mineral resources are on the verge of depletion, the current price of tungsten carbide raw materials has also risen, resulting in high costs for cemented carbide rods.
[0003] Therefore, in order to ensure the sustainable development of the cemented carbide industry, it is urgent to develop an economical, high-hardness, high-bending strength, and superior-performance recycled tungsten carbide-based cemented carbide.
[0004] Application Contents
[0005] The present application is made in view of the above-mentioned problems, and an object of the present application is to provide a cemented carbide material having high bending strength.
[0006] Specifically as follows, the first aspect of the present application provides a recycled cemented carbide material for round rods, comprising cobalt and tungsten carbide;
[0007] The mass fraction of the cobalt is 10% to 15%.
[0008] According to one of the technical solutions of this application, at least the following beneficial effects are achieved:
[0009] The present application reduces the amount of primary tungsten carbide in the alloy material, thereby not only effectively reducing the production cost, but also maintaining the superior comprehensive performance of high hardness and high bending strength.
[0010] According to some embodiments of the present application, the sources of the tungsten carbide are electrolytic tungsten carbide and YG zinc melt.
[0011] According to some embodiments of the present application, the electrolytic tungsten carbide has a Fisher particle size of 1.0 μm to 1.5 μm.
[0012] According to some embodiments of the present application, the Fisher particle size of the YG zinc melt is 0.8 μm to 1.2 μm.
[0013] According to some embodiments of the present application, the cobalt powder has a Fisher particle size of 1.0 μm to 1.5 μm.
[0014] The present application finds that by using the mutual coordination of regenerated tungsten carbide, zinc melt and cobalt powder of specific mass and Fisher grain size, and combining regenerated tungsten carbide and zinc melt of different contents and grain sizes, after sintering, the fine grains in the internal structure of the alloy fill each other to form a denser structure, thereby significantly improving the strength on the basis of the high hardness of the fine-grained alloy, so that the prepared cemented carbide can have good hardness and bending strength at the same time.
[0015] According to some embodiments of the present application, the average grain size of tungsten carbide in the cemented carbide material is 0.8 μm to 1.0 μm.
[0016] According to some embodiments of the present application, the porosity of the cemented carbide material is A02B00C00.
[0017] According to some embodiments of the present application, the average bending strength of the cemented carbide material is above 2600 MPa.
[0018] According to some embodiments of the present application, the average bending strength of the cemented carbide material is between 2600 MPa and 2800 MPa.
[0019] According to some embodiments of the present application, the average hardness (HRA) of the cemented carbide material is 90 or more.
[0020] According to some embodiments of the present application, the average hardness (HRA) of the cemented carbide material is 90-92.
[0021] According to some embodiments of the present application, the average hardness (HRA) of the cemented carbide material is 90.5-91.2.
[0022] According to some embodiments of the present application, the YG zinc melt includes the following components in mass fractions: Co: 5% to 13% and WC: 86% to 94%.
[0023] The second aspect of the present application provides a method for preparing the above-mentioned recycled cemented carbide material for round rods, comprising the following steps:
[0024] S1. Mixing tungsten carbide raw material and cobalt powder to obtain powder;
[0025] S2, mixing the powder and the forming agent to obtain a mixture;
[0026] S3, forming the mixed material and then sintering;
[0027] The tungsten carbide raw material includes electrolytic tungsten carbide and YG zinc melt;
[0028] The sintering temperature is 350°C to 1500°C.
[0029] According to one of the technical solutions of this application, at least the following beneficial effects are achieved:
[0030] The preparation method is simple and easy, suitable for large-scale production, and the obtained cemented carbide material is strong and durable. It makes full use of waste in industry, construction and daily life, realizes the effective transformation of resources, and reduces the waste of material energy and environmental pollution.
[0031] According to some embodiments of the present application, the powder is composed of the following raw materials by weight:
[0032] 93%~98% tungsten carbide raw material and 2%~7% cobalt powder.
[0033] According to some embodiments of the present application, the powder is composed of the following raw materials by weight:
[0034] Electrolytic tungsten carbide: 10%~15%, YG zinc melt: 78%~88% and cobalt powder: 2%~7%.
[0035] According to some embodiments of the present application, the mass ratio of the mixture to the forming agent is 97.5-99.0:1.0-2.5.
[0036] According to some embodiments of the present application, the mass ratio of the mixture to the forming agent is 98.4:1.6.
[0037] According to some embodiments of the present application, the molding agent includes at least one of 2C, paraffin and rubber.
[0038] According to some embodiments of the present application, the mixing in step S1 includes wet grinding, drying and sieving.
[0039] According to some embodiments of the present application, the wet milling is to mix the ball milling media, carbide balls and the mixed material and then mill them.
[0040] According to some embodiments of the present application, the ball milling medium is ethanol.
[0041] According to some embodiments of the present application, the cemented carbide ball is YG alloy.
[0042] According to some embodiments of the present application, the mass ratio of the mixture to the ball milling medium is 3 to 6:1.
[0043] According to some embodiments of the present application, the mass ratio of the mixture to the ball milling medium is 3:1.
[0044] According to some embodiments of the present application, the mass ratio of the mixture to the cemented carbide ball is 1:3-6.
[0045] According to some embodiments of the present application, the mass ratio of the mixture to the cemented carbide ball is 1:3.
[0046] According to some embodiments of the present application, the wet grinding time is 30 h to 60 h.
[0047] According to some embodiments of the present application, the mixing in step S2 is followed by sieving.
[0048] The operation of sieving after mixing is conventional in the art. Preferably, the wet-milled and dried powder is sieved and placed in a 30L spiral mixer, stirred while mixing with the molding agent, and placed on a grating sieve for sieving after drying. The purpose of sieving after mixing is to form a mixture of different particle sizes to facilitate adaptation to different pressing equipment.
[0049] The operation and conditions of the press forming are the conventional press forming operations and conditions in the art. The press forming can select a suitable mold according to the shape specifications of the recycled cemented carbide material required for the round rod.
[0050] According to some embodiments of the present application, the sintering in step S3 sequentially includes dewaxing, vacuum heating, partial pressure heating and pressurized heating.
[0051] Sintering is conventional in the art. Preferably, the pressed green compact is placed on a graphite boat, and sintered into a cemented carbide material by dewaxing, vacuum heating, partial pressure heating and pressure heating in a vacuum integrated sintering furnace.
[0052] According to some embodiments of the present application, the heating rate of the dewaxing is 0.5°C / min to 3.0°C / min.
[0053] According to some embodiments of the present application, the dewaxing includes a first heat preservation dewaxing, a second heat preservation dewaxing and a third heat preservation dewaxing.
[0054] According to some embodiments of the present application, the temperature of the first thermal insulation dewaxing is 350°C to 400°C.
[0055] According to some embodiments of the present application, the temperature of the first thermal insulation dewaxing is 360°C.
[0056] According to some embodiments of the present application, the time of the first thermal insulation dewaxing is 1.5h to 2.5h.
[0057] According to some embodiments of the present application, the first thermal insulation dewaxing time is 2 hours.
[0058] According to some embodiments of the present application, the temperature of the second thermal insulation dewaxing is 450°C to 500°C.
[0059] According to some embodiments of the present application, the temperature of the second thermal insulation dewaxing is 480°C.
[0060] According to some embodiments of the present application, the second thermal insulation dewaxing time is 1.5h to 2.5h.
[0061] According to some embodiments of the present application, the second thermal insulation dewaxing time is 2 hours.
[0062] According to some embodiments of the present application, the temperature of the third thermal insulation dewaxing is 550°C to 600°C.
[0063] According to some embodiments of the present application, the temperature of the third thermal insulation dewaxing is 590°C.
[0064] According to some embodiments of the present application, the time for the third thermal insulation dewaxing is 1.5h to 2.5h.
[0065] According to some embodiments of the present application, the third thermal insulation dewaxing time is 2 hours.
[0066] According to some embodiments of the present application, the maximum temperature of the dewaxing is 700°C to 800°C.
[0067] According to some embodiments of the present application, the maximum temperature of dewaxing is 800°C.
[0068] According to some embodiments of the present application, the dewaxing time is 15 h to 20 h.
[0069] According to some embodiments of the present application, the dewaxing time is 16 hours.
[0070] According to some embodiments of the present application, the heating rate of the vacuum heating is 2.5°C / min to 3.5°C / min.
[0071] According to some embodiments of the present application, the vacuum heating includes a vacuum heating insulation stage.
[0072] According to some embodiments of the present application, the temperature of the vacuum heating and insulation stage is 1150°C to 1200°C.
[0073] According to some embodiments of the present application, the temperature of the vacuum heating and insulation stage is 1150°C.
[0074] According to some embodiments of the present application, the maximum temperature of the vacuum heating is 1300°C to 1400°C.
[0075] According to some embodiments of the present application, the vacuum heating time is 4 hours to 5 hours.
[0076] According to some embodiments of the present application, the vacuum heating time is 4.5 hours.
[0077] According to some embodiments of the present application, the pressure of the vacuum heating is 0.5 mbar to 1 mbar.
[0078] According to some embodiments of the present application, the pressure of the vacuum heating is 0.8 mbar.
[0079] According to some embodiments of the present application, the temperature of the partial pressure heating is 1400°C to 1450°C.
[0080] According to some embodiments of the present application, the temperature of the partial pressure heating is 1400°C or 1430°C.
[0081] According to some embodiments of the present application, the partial pressure heating time is 0.5h to 1h.
[0082] According to some embodiments of the present application, the partial pressure heating time is 0.8 h.
[0083] According to some embodiments of the present application, the pressure of the partial pressure heating is 30 mbar to 50 mbar.
[0084] According to some embodiments of the present application, the pressure of the partial pressure heating is 40 mbar.
[0085] According to some embodiments of the present application, the temperature of the pressurized heating is 1400°C to 1450°C.
[0086] According to some embodiments of the present application, the temperature of the pressurized heating is 1400°C or 1430°C.
[0087] According to some embodiments of the present application, the pressurized heating time is 0.5h to 1h.
[0088] According to some embodiments of the present application, the pressurized heating time is 0.67 h.
[0089] According to some embodiments of the present application, the pressure of the pressurization and heating is 40 bar to 60 bar.
[0090] According to some embodiments of the present application, the pressure of the pressurization and heating is 50 bar.
[0091] On the basis of conforming to the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present application.
[0092] The reagents and raw materials used in this application are commercially available.
[0093] The significant progress of this application is reflected in the following aspects:
[0094] The proportion of non-virgin materials used in the present application in the mixed materials is 93% to 98%, which fully reflects the high utilization rate of recycled materials and promotes green environmental protection and energy conservation.
[0095] The cemented carbide material in the present application is formed into an alloy with a tight internal structure through the synergistic effect of electrolytic carbides, YG zinc melt and cobalt powder in a specific ratio and specific Fehler particle size, and a combination of recycled tungsten carbide and zinc melt with different contents and particle sizes, and sintering. This process effectively improves the bending strength of the alloy on the basis of the original fine grains, so that the prepared cemented carbide has both excellent hardness and bending strength.
[0096] In the prepared cemented carbide material, the average grain size of WC is 1.0 μm, the porosity is A02B00C00, the average bending strength is between 2600 and 2800 MPa, and the average hardness is HRA 90.5 to 91.0;
[0097] In some preferred embodiments, the average grain size of WC can be reduced to 0.8 μm, the bending strength reaches 2800 MPa, the hardness HRA is increased to 91.2, and the metallographic characteristics are A02B00C00.
[0098] The present application successfully solves the problem of difficulty in achieving both high hardness and high bending strength when preparing cemented carbide from recycled tungsten carbide through the coordinated application of specific ratios and particle sizes of electrolytic carbides, YG zinc melt and cobalt powder.
[0099] The process flow of the present application is simple and easy to control, with low production cost. The product produced not only has high hardness and strength, but also can effectively meet the use requirements of round rods. BRIEF DESCRIPTION OF THE DRAWINGS
[0100] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0101] Figure 1 This is a typical EDS spectrum of the round rod prepared in Example 2.
[0102] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION
[0103] The following description will be appropriately detailed for the embodiments specifically disclosed in the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0104] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3,4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0105] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0106] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0107] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0108] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0109] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0110] The electrolytic tungsten carbide selected in the examples and comparative examples of the present application is mainly composed of tungsten carbide, with the remainder being inevitable impurities (with a purity of more than 99.9%).
[0111] The mass fraction of Co in the YG zinc melt is 10% and WC is 89%, and the remainder is trace impurity elements.
[0112] The purity of Co powder is 99.9%.
[0113] Example 1
[0114] This embodiment is a recycled cemented carbide material for round rods, the alloy grain size is uniform, the WC average grain size is 1.0 μm, the porosity is A02B00C00, the average bending strength is 2600 MPa, and the average hardness is HRA90.6.
[0115] The composition of the powder of this embodiment is as follows: a raw material containing 10.8% cobalt by mass and the remainder being tungsten carbide and inevitable impurities.
[0116] The powder material of this embodiment is composed of the following raw materials by mass fraction:
[0117] Electrolytic tungsten carbide 10%, YG zinc melt 88% and cobalt powder 2%.
[0118] Among them, the Fischer-Tropsch particle size of electrolytic tungsten carbide is 1.3μm, the Fischer-Tropsch particle size of YG zinc melt is 0.8μm, and the Fischer-Tropsch particle size of cobalt powder is 1.3μm.
[0119] The preparation method of the recycled cemented carbide material for round rods in this embodiment consists of the following steps:
[0120] S1, mixing electrolytic tungsten carbide, YG zinc melt and cobalt powder to obtain raw materials;
[0121] S2. Place the raw materials in a ball mill for mixed wet grinding, add wet grinding medium ethanol (the mass ratio of the raw material to the wet grinding medium is 3:1) and cemented carbide ball YG alloy (the mass ratio of the raw material to the cemented carbide ball is 1:3), wet grind for 48 hours to obtain powder, pour the powder into a vacuum stirring dryer for drying, and pass the dried material through an 80-mesh sieve on a Fangmei vibrating screen.
[0122] S3, the sieved powder is placed in a 30L spiral mixer, mixed with 2C molding agent while stirring (the mass ratio of raw material to molding agent is 98.4:1.6), and after drying, it is placed on a grating sieve for grating to obtain a mixture;
[0123] S4, pressing the mixed material into a compact;
[0124] S5. The pressed green compact is placed on a graphite boat, and dewaxed, vacuum heated, partially heated, and pressurized in an overpressure sintering furnace.
[0125] Dewaxing includes the first heat preservation dewaxing, the second heat preservation dewaxing and the third heat preservation dewaxing;
[0126] The temperature of the first thermal insulation dewaxing is 360℃;
[0127] The first heat preservation and dewaxing time is 2h;
[0128] The temperature of the second thermal insulation dewaxing is 480°C;
[0129] The second heat preservation and dewaxing time is 2h;
[0130] The temperature of the third thermal insulation dewaxing is 590°C;
[0131] The third heat preservation and dewaxing time is 2h;
[0132] The maximum dewaxing temperature is 800°C;
[0133] The total dewaxing time was 16 h (heating rate was 1 °C / min to 1.5 °C);
[0134] After dewaxing, the temperature is raised to 1150°C at a heating rate of 2.5°C / min to 3.5°C / min for vacuum sintering. The temperature is kept at 1150°C for 1 hour. After the temperature is kept, the temperature is raised to 1350°C. The pressure of vacuum sintering is 0.8 mbar. The total time of vacuum sintering is 4.5 hours.
[0135] After vacuum sintering, the temperature is raised to 1450°C for partial pressure heating (heating rate of 2.5°C / min to 3.5°C / min). The temperature of partial pressure heating is 1450°C, the pressure of partial pressure heating is 40mbar, and the time of partial pressure heating is 0.8h.
[0136] After the partial pressure heating is completed, the pressure is increased to 50 bar for pressure heating. The pressure of the pressure heating is 50 bar, the temperature of the pressure heating is 1450°C, and the time of the pressure heating is 0.67 h. After the pressure heating is completed, the recycled cemented carbide material for round rods is obtained.
[0137] Example 2
[0138] This embodiment is a recycled cemented carbide material for round rods. The alloy has uniform grain size, an average WC grain size of 1.0 μm, a porosity of A02B00C00, an average bending strength of 2650 MPa, and an average hardness of HRA90.5. Figure 1 This is a typical EDS spectrum of the round rod prepared in Example 2.
[0139] The composition of the powder in this embodiment is as follows: a raw material having a mass fraction of 13.2% cobalt and the balance being tungsten carbide and inevitable impurities.
[0140] The powder material of this embodiment is composed of the following raw materials by mass fraction:
[0141] Electrolytic tungsten carbide 13%, YG zinc melt 82% and cobalt powder 5%.
[0142] Among them, the Fischer-Tropsch particle size of electrolytic tungsten carbide is 1.3μm, the Fischer-Tropsch particle size of YG zinc melt is 0.8μm, and the Fischer-Tropsch particle size of cobalt powder is 1.3μm.
[0143] The preparation method of the recycled cemented carbide material for round rods in this embodiment is different from that in Embodiment 1 only in that:
[0144] The temperature of partial pressure heating is 1430℃;
[0145] The temperature of the pressurized heating was 1430°C.
[0146] Example 3
[0147] This embodiment is a recycled cemented carbide material for round rods, the alloy grain size is uniform, the WC average grain size is 0.8 μm, the porosity is A02B00C00, the average bending strength is 2800 MPa, and the average hardness is HRA 91.0.
[0148] The composition of the powder of this embodiment is as follows: a raw material containing 14.8% cobalt by mass and the remainder being tungsten carbide and inevitable impurities.
[0149] The powder material of this embodiment is composed of the following raw materials by mass fraction:
[0150] Electrolytic tungsten carbide 15%, YG zinc melt 78% and cobalt powder 7%.
[0151] Among them, the Fischer-Tropsch particle size of electrolytic tungsten carbide is 1.2μm, the Fischer-Tropsch particle size of YG zinc melt is 0.8μm, and the Fischer-Tropsch particle size of cobalt powder is 1.0μm.
[0152] The temperature of partial pressure heating is 1410℃;
[0153] The temperature of the pressurized heating was 1410°C.
[0154] Comparative Example 1
[0155] This comparative example is a recycled cemented carbide material for round rods, the alloy grain size is uniform, the WC average grain size is 1.1 μm, the porosity is A02B00C00, the average bending strength is 2560 MPa, and the average hardness is HRA 90.4.
[0156] The composition of the powder of this comparative example is as follows: a raw material containing 9.5% cobalt by mass and the remainder being tungsten carbide and inevitable impurities.
[0157] The powder of this comparative example is composed of the following raw materials by mass fraction:
[0158] Electrolytic tungsten carbide 50%, YG zinc melt 45% and cobalt powder 5%.
[0159] Among them, the Fischer-Tropsch particle size of electrolytic tungsten carbide is 1.3μm, the Fischer-Tropsch particle size of YG zinc melt is 0.8μm, and the Fischer-Tropsch particle size of cobalt powder is 1.3μm.
[0160] Comparative Example 2
[0161] This comparative example is a recycled cemented carbide material for round rods, the alloy grain size is uniform, the WC average grain size is 1.1 μm, the porosity is A02B00C00, the average bending strength is 2550 MPa, and the average hardness is HRA 90.8.
[0162] The composition of the powder of this comparative example is as follows: a raw material having a mass fraction of 13% cobalt and the balance being tungsten carbide and inevitable impurities.
[0163] The powder of this comparative example is composed of the following raw materials by mass fraction:
[0164] Electrolytic tungsten carbide 6%, YG zinc melt 90% and cobalt powder 4%.
[0165] Among them, the Fischer-Tropsch particle size of electrolytic tungsten carbide is 1.3μm, the Fischer-Tropsch particle size of YG zinc melt is 0.8μm, and the Fischer-Tropsch particle size of cobalt powder is 1.3μm.
[0166] Comparative Example 3
[0167] This comparative example is a recycled cemented carbide material for round rods, the alloy grain size is uniform, the WC average grain size is 1.2μm, the porosity is A02B00C00, the average bending strength is 2600MPa, and the average hardness is HRA90.3.
[0168] The composition of the powder of this comparative example is as follows: a raw material containing 14.7% cobalt by mass and the remainder being tungsten carbide and inevitable impurities.
[0169] The powder of this comparative example is composed of the following raw materials by mass fraction:
[0170] Electrolytic tungsten carbide 70%, YG zinc melt 17% and cobalt powder 13%.
[0171] Among them, the Fischer-Tropsch particle size of electrolytic tungsten carbide is 1.2μm, the Fischer-Tropsch particle size of YG zinc melt is 0.8μm, and the Fischer-Tropsch particle size of cobalt powder is 1.0μm.
[0172] The present application aims to solve the problem that the existing tungsten carbide-based cemented carbide production cost is high and the tungsten carbide-based cemented carbide material prepared from recycled materials is difficult to achieve high hardness and high strength at the same time, and to provide a new type of tungsten carbide-based cemented carbide and its preparation method. The alloy not only effectively reduces the production cost by reducing the amount of original tungsten carbide, but also maintains the superior comprehensive performance of high hardness and high bending strength.
[0173] At present, in the preparation process of tungsten carbide cemented carbide, recycled tungsten carbide is usually added to reduce costs. However, the alloy obtained is difficult to have both high hardness and high bending strength. The cemented carbide prepared from recycled materials basically used for round bars has a hardness HRA of more than 90, but the bending strength is only in the range of 2000MPa to 2500MPa.
[0174] After in-depth research, the applicant found that by using the combination of recycled tungsten carbide of specific mass and Fisher grain size, zinc melt and cobalt powder, combined with recycled tungsten carbide and zinc melt of different contents and grain sizes, after sintering, the fine grains in the internal structure of the alloy fill each other to form a denser structure, thereby significantly improving the strength on the basis of the high hardness of the fine-grained alloy, so that the prepared cemented carbide can have good hardness and bending strength at the same time. Based on this, further research was carried out to complete this application.
[0175] The preparation method is simple and easy, suitable for large-scale production, and the obtained cemented carbide material is strong and durable. It makes full use of waste in industry, construction and daily life, realizes the effective transformation of resources, and reduces the waste of material energy and environmental pollution.
[0176] The specific embodiments described above further explain the purpose, technical solutions and beneficial effects of the present application in detail. It should be understood that the above description is only a specific embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
[0177] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A recycled cemented carbide material for round bars, characterized in that: Includes cobalt and tungsten carbide; The mass fraction of the cobalt is 10% to 15%.
2. The recycled cemented carbide material for round rods according to claim 1, characterized in that: The sources of the tungsten carbide are electrolytic tungsten carbide and YG zinc melt.
3. The recycled cemented carbide material for round rods according to claim 2, characterized in that: The electrolytic tungsten carbide has a particle size of 1.0 μm to 1.5 μm; And / or, the Fischer-Strauss particle size of the YG zinc melt is 0.8 μm to 1.2 μm; And / or, the cobalt powder has a Fisher particle size of 1.0 μm to 1.5 μm.
4. The method for preparing recycled cemented carbide material for round rods according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Mixing tungsten carbide raw material and cobalt powder to obtain powder; S2, mixing the powder and the forming agent to obtain a mixture; S3, forming the mixed material and then sintering; The tungsten carbide raw material includes electrolytic tungsten carbide and YG zinc melt; The sintering temperature is 350°C to 1500°C.
5. The preparation method according to claim 4, characterized in that: The powder is composed of the following raw materials by weight: 93%~98% tungsten carbide raw material and 2%~7% cobalt powder; And / or, the powder is composed of the following raw materials in weight fractions: Electrolytic tungsten carbide: 10%~15%, YG zinc melt: 78%~88% and cobalt powder: 2%~7%; and / or, the mass ratio of the mixed material to the molding agent is 97.5-99.0:1.0-2.5; And / or, the molding agent includes at least one of 2C, paraffin and rubber.
6. The preparation method according to claim 4, characterized in that: The mixing in step S1 includes wet grinding, drying and sieving; And / or, the wet grinding is to mix the ball milling medium, the carbide balls and the mixed material and then grind them; And / or, the ball milling medium is ethanol; And / or, the cemented carbide ball is YG alloy; and / or, the mass ratio of the mixed material to the ball milling medium is 3 to 6:1; and / or, the mass ratio of the mixture to the cemented carbide ball is 1:3-6; And / or, the wet grinding time is 30h to 60h.
7. The preparation method according to claim 4, characterized in that: After mixing in step S2, sieve.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The sintering in step S3 includes dewaxing, vacuum heating, partial pressure heating and pressurized heating in sequence; And / or, the heating rate of the dewaxing is 0.5°C / min to 3.0°C / min; And / or, the dewaxing includes a first heat preservation dewaxing, a second heat preservation dewaxing and a third heat preservation dewaxing; And / or, the temperature of the first thermal insulation dewaxing is 350° C. to 400° C.; And / or, the temperature of the second thermal insulation dewaxing is 450° C. to 500° C.; And / or, the temperature of the third thermal insulation dewaxing is 550° C. to 600° C.; And / or, the maximum temperature of the dewaxing is 700° C. to 800° C.; And / or, the dewaxing time is 15h to 20h.
9. The preparation method according to claim 8, characterized in that: The heating rate of the vacuum heating is 2.5°C / min to 3.5°C / min; And / or, the vacuum heating includes a vacuum heating and heat preservation stage; And / or, the temperature in the vacuum heating and heat preservation stage is 1150° C. to 1200° C.; And / or, the maximum temperature of the vacuum heating is 1300° C. to 1400° C.; And / or, the vacuum heating time is 4h to 5h; And / or, the vacuum heating pressure is 0.5 mbar to 1 mbar.
10. The preparation method according to claim 8, characterized in that: The temperature of the partial pressure heating is 1400°C to 1450°C; And / or, the partial pressure heating time is 0.5h to 1h; And / or, the pressure of the partial pressure heating is 30 mbar to 50 mbar; And / or, the temperature of the pressurized heating is 1400-1450°C; And / or, the pressurized heating time is 0.5h to 1h; And / or, the pressure of the pressurization and heating is 40 bar to 60 bar.